الإرهاب الدولي وسبل معالجته ومقاومته ، دراسة تحليلية على عينة من برامج الجزيرة إبان الأزمة الجزائرية . - لمطاعي, فيروز (جامعة الوادي - University of Eloued, 2021)
تبحث هذه الدّراسة التطبيقية في موضوع الإرهاب الدولي وسبل معالجته ومقاومته، والتي تعتبر من المواضيع الشائكة التي تحتاج لدراسات تطبيقية عميقة، وذلك من خلال دراسة تحليلية تطبيقية على عينة من برامج الجزيرة إبان الأزمة الجزائرية. وتعرج الدراسة على علاقة الإعلام والسياسة بالإرهاب من خلال التركيز على أبرز الأحداث السياسية ودراسة علاقتها بالإرهاب إبان الأزمة الجزائرية، بداية بالأزمة الاقتصادية، والسياسية وصولا للمصالحة الوطنية. فأمام تقلص المسافات في العالم أو في القرية الصغيرة التي تخيلها مارشال ماكلوهان على مدى عصور كجزءٍ من المجهول ، أصبحت بفضل وسائل الإعلام حقيقة هذه المرحلة وتداعياتها السياسية والاجتماعية في أجندة كل المواعيد الإخبارية والصحف والمجلات السياسية مثلما كانت وسائل الإعلام سببا في تهويل الأوضاع في دول الربيع العربي بعد ذلك. تقوم الدراسة بتحليل أبرز البرامج السياسية التي بثتها فضائية الجزيرة الإخبارية منذ انطلاق بثها العام 1996 والتي تعتبر أكثر السنوات دموية في الجزائر وصولا لما بعد عشرية الإرهاب. واعتمدت الدراسة على المنهج الوصفي التحليلي الذي يقوم على وصف الظاهرة وتحليلها باستخدام أداة تحليل المضمون ، من خلال دراسة وتحليل مضمونها ومواضيعها التي تستضيف شخصيات سياسية ،وشهود عيان،ومؤرخين ،وخبراء استراتيجيين وغيرهم ، واختيار عينة قصدية لهذه البرامج بناءا على أهميتها وثقل وزن ضيوفها . This study examines the issue of international terrorism and means of treating and resisting it, which are considered thorny topics that need in-depth applied studies, through an applied analytical study on a sample of Al-Jazeera programs during the Algerian crisis. The study delves into the relationship of the media and politics to terrorism by focusing on the most prominent political events and studying its relationship with terrorism during the Algerian crisis, beginning with the economic and political crisis and leading to national reconciliation. In the face of shrinking distances in the world or in the small village that Marshall McLuhan imagined over the ages as part of the unknown, thanks to the media, the reality of this stage and its political and social implications have become in the agenda of all news appointments, newspapers and political magazines, just as the media was a reason to exaggerate the situation in the Arab Spring countries. The study analyzes the most prominent political programs broadcast by the Al-Jazeera news channel since the launch of its broadcast in 1996, which is considered the bloodiest year in Algeria, all the way to the post-ten years of terrorism. The study relied on the descriptive and analytical approach that is based on describing the phenomenon and analyzing it using the content analysis tool, by studying and analyzing its content and topics that host political figures, eyewitnesses, historians, strategic experts and others, and choosing an intentional sample for these programs based on their importance and the weight of their guests.
International terrorism and means of treating and resisting it, analytical study on a sample of Al-Jazeera programs during the Algerian crisis
مقال
Keywords: الإرهاب ، العشرية السوداء ، المصالحة الوطنية ، الفضائيات العربية ، البرامج السياسية ، فضائية الجزيرة .; Terrorism, the Black Decade ,National Reconciliation, Arab satellite channels, Political Programs, Al Jazeera Channel.